Utilization of Selected Underexploited Fruits for Product Development - Teena Joy (Department of Home Science, College of Horticulture, 2003)
In the present study entitled "Utilization of selected underexplotied fruits for product development" include developing products from underexploited fruits like bilimbi, roseapple (rose and white types) and lovi-Iovi (sweet and sour type). The products prepared from these fruits were bilimbi jam, bilimbi pickle, roseapple squash (rose), roseapple squash (white), lovi-Iovi preserve in sugar and lovi-Iovi in brine. Physico-chemical examination of the fruits indicated wide difference in characters among the selected fruits. Regarding the sensory evaluation of the fruits, roseapple (rose) had highest overall acceptability followed by roseapple (white), lovi- lovi (sweet), lovi-lovi (sour) and the least bilimbi. All the products developed in the present study confirmed with FPO specifications. Cost analysis of the products indicated lowest cost for lovi- lovi in brine and the maximum expense for lovi-lovi preserve in sugar. Roseapple (rose and white) squashes exhibited high fruit product yield ratio followed by bilimbi jam, lovi-lovi.preserve in sugar, lovi-lovi in brine and bilimbi pickle. The major chemical components analysed in the products developed from the selected fruits were TSS, acidity, vitamin C, reducing, non reducing and total sugar. During the storage period of six months, TSS, acidity, reducing and total sugars were found to be increased gradually in bilimbi jam and rose and white roseapple squashes while